2007
DOI: 10.1590/s1413-80502007000300006
|View full text |Cite
|
Sign up to set email alerts
|

Investigação do desempenho das cooperativas de crédito de Minas Gerais por meio da Análise Envoltória de Dados (DEA)

Abstract: Este trabalho buscou investigar o desempenho das Cooperativas de Economia e Crédito Mútuo de Minas Gerais, fundamentando-se no conceito de eficiência e considerando o seu papel de instituições de desintermediação financeira entre os seus membros associados. A mensuração da eficiência deu-se por meio da Análise Envoltória de Dados (DEA), a partir de indicadores contábeis e financeiros de 105 cooperativas de crédito que compuseram o escopo da pesquisa, no ano de 2003. Os fatores condicionantes da eficiência fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
27

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 28 publications
0
15
0
27
Order By: Relevance
“…They reduce bank interests, especially overdraft fees and loans. However, regarding financial services, they differ from other financial institutions by their goals, and the public they want to achieve (Ferreira, Gonçalves, & Braga, 2007). Sales (2010) ensures that the basis of the existence of a cooperative is the conjunction of individuals joining in a cooperative manner, who have common purposes and interests.…”
Section: Cooperatives In Economic Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…They reduce bank interests, especially overdraft fees and loans. However, regarding financial services, they differ from other financial institutions by their goals, and the public they want to achieve (Ferreira, Gonçalves, & Braga, 2007). Sales (2010) ensures that the basis of the existence of a cooperative is the conjunction of individuals joining in a cooperative manner, who have common purposes and interests.…”
Section: Cooperatives In Economic Contextmentioning
confidence: 99%
“…The cooperatives are an alternative to meeting the demand for credit in the market, due to a third of Brazilian municipalities with no bank branches. Ferreira, Gonçalves, and Braga (2007) assert that, although the participation of cooperatives in the operations is still small compared to the Brazilian national banking system, their consistent growth demonstrates the importance of the sector. Accordingly, the analysis of the performance of the cooperatives becomes relevant, insofar as incentives for expanding the sector differ from other financial institutions.…”
Section: Introductionmentioning
confidence: 98%
“…Os índi-ces de estrutura evidenciam a composição dos capitais próprios e de terceiros que financiam os investimentos da empresa, refletindo assim a sua estrutura de capital e suas decisões de investimento e financiamento. Já os indicadores eficiência econômica, representado pelos índices de lucratividade, visam identificar a situação econômica das empresas pois fornecem o retorno proporcionado pelo negócio, sinalizando a eficiência da sua gestão (Damodaran, 2002;Ferreira, 2005;Assaf Neto, 2012 avaliar quantas e quais DMU´s são eficientes e aquelas que não são eficientes e, para as não eficientes, apresenta as DMU´s que lhes servem de referência para aumento de eficiência (Ferreira, Gonçalves & Braga, 2007;Macedo, Barbosa & Cavalcante, 2009 O modelo BCC permite a projeção de cada DMU ineficiente sobre a superfície de fronteira (envoltória) determinada pelas DMU´s eficientes de tamanho compatível. Como o DEA® produz um indicador que varia de 0 a 1, então foi aplicado o método para todo o conjunto de empresas que compõe a amostra do estudo, permitindo assim a identificação e comparação das empresas eficientes.…”
Section: Procedimentos De Coleta E Análise De Dadosunclassified
“…Evaluating the economic situation of rural credit unions from Minas Gerais, Brazil, Braga et al (2006) showed that it is possible to obtain the information needed to monitor these institutions. Ferreira, Gonçalves and Braga (2007) used data envelopment analysis and the Tobit method to investigate the determinants of the efficiency of these entities and found evidence that credit unions often do not use their resources efficiently. Davis (2001) investigated the importance of the relation between the principle "one member, one vote" to the survival of credit unions, arguing that as older members have greater participation in funds, they have greater incentives to attempt extracting the maximum benefits by transforming these institutions into for-profit corporations.…”
Section: Literature Reviewmentioning
confidence: 99%